Social Health Insurance vs. Tax-Financed Health Systems—Evidence from the OECD - Wagstaff, Adam (2012)
This paper exploits the transitions between tax-financed health care and social health insurance in the OECD countries over the period 1960-2006 to assess the effects of adopting social health insurance over tax finance on per capita health spending, amenable mortality, and labor market outcomes. The paper uses regression-based generalizations of difference-in-differences and instrumental variables to address the possible endogeneity of a country's health system. It finds that adopting social health insurance in preference to tax financing increases per capita health spending by 3-4 percent, reduces the formal sector share of employment by 8-10 percent, and reduces total employment by as much as 6 percent. For the most part, social health insurance adoption has no significant impact on amenable mortality, but for one cause-breast cancer among women-social health insurance systems perform significantly worse, with 5-6 percent more potential years of life lost.